 # Solving multi step equations. 12X + 3 = 4X + 27 - X 12X + 3 = 3X + 27 -3X 9X + 3 = 27 -3 9X = 24 99 X = 2.6 1.

## Presentation on theme: "Solving multi step equations. 12X + 3 = 4X + 27 - X 12X + 3 = 3X + 27 -3X 9X + 3 = 27 -3 9X = 24 99 X = 2.6 1."— Presentation transcript:

Solving multi step equations

12X + 3 = 4X + 27 - X 12X + 3 = 3X + 27 -3X 9X + 3 = 27 -3 9X = 24 99 X = 2.6 1

8 – (2 – 2X) = -4X + 3(4X + 5) 8 -2 + 2X = -4X + 12X + 15 6 + 2X = 8X + 15 -2X 6 = 6X + 15 -15 -9 = 6X 66 X = - 1.5 1 -2 + 2X= + 12X + 15 68X

2 – 15n = 5(-3n + 2) 2 – 15n = -15n + 10 +15n 2 = 10 2 can’t equal 10 so this equation has no solution

5(1 + 4m) = 2(2.5 + 10m) 5 + 20m = 5 + 20m -20m 5 = 5 5 will always equal 5 so this equation has all solutions or infinitely many solutions

Page 437 1 – 9 all

12X + 3 = 4X + 27 - X = = = X =

8 – (2 – 2X) = -4X + 3(4X + 5) = = = = X =

2 – 15n = 5(-3n + 2) = = ____ can’t equal ____ so this equation has ___________

5(1 + 4m) = 2(2.5 + 10m) = = ____ will always equal _____ so this equation has _____________ or ______________________

Download ppt "Solving multi step equations. 12X + 3 = 4X + 27 - X 12X + 3 = 3X + 27 -3X 9X + 3 = 27 -3 9X = 24 99 X = 2.6 1."

Similar presentations